The seventy great inventions of the ancient world - Fagan, Brian M. (London : Thames & Hudson, 2004)
Stone choppers, eyed needles, camel saddles, chariots, and contraceptives: the past is paved with remarkable inventions. The latest book in this popular series takes us on an eye-opening and unusual journey through early human innovations--some fundamental and others intriguing or bizarre. An international team of scientists, archaeologists, and historians reveals seventy of the most extraordinary inventions, from two-and-a-half million years ago up to the early medieval period. The book begins with the basic technologies of stone, fire, woodworking, ceramics, metallurgy, glass, and weaving. We watch Stone Age flint-knappers at work and look over the shoulders of early metalworkers as they fabricate glittering ornaments in copper and gold. Some of the most fundamental questions of the past are addressed. How and where did agriculture evolve? How did Romans and others heat and plumb their dwellings? What roles did cooking, food preservation, and fermentation play in the development of ancient cuisine? How did the wheel and cart change human life? When did the first roads appear, and when did long-distance seafaring begin? Later sections look at the origins of hunting, war and sport, art and science, and personal adornment. Weapons of war evolved from spears, bows, and arrows to swords, shields, catapults, and crossbows.
Includes bibliographical references (p. 291-296) and index.
Keywords: Inventions -- History; Technology -- History